Resisting Visual, Phonological, and Semantic Interference – Same or Different Processes? A Focused Mini-Review - Coline Grégoire; Steve Majerus (Psychologica Belgica, 2023)
The unitary nature of resistance to interference (RI) processes remains a strongly debated question: are they central cognitive processes or are they specific to the stimulus domains on which they operate? This focused mini-review examines behavioral, neuropsychological and neuroimaging evidence for and against domain-general RI processes, by distinguishing visual, verbal phonological and verbal semantic domains. Behavioral studies highlighted overall low associations between RI capacity across domains. Neuropsychological studies mainly report dissociations for RI abilities between the three domains. Neuroimaging studies highlight a left vs. right hemisphere distinction for verbal vs. visual RI, with furthermore distinct neural processes supporting phonological versus semantic RI in the left inferior frontal gyrus. While overall results appear to support the hypothesis of domain-specific RI processes, we discuss a number of methodological caveats that ask for caution in the interpretation of existing studies.